Dynamics of Power and Politics in Ibn Khaldun's Social Philosophy - Erman, Mulyadi; Junaidi, Junaidi (PT. Riset Press International, 2024)
This research examines Ibn Khaldun's social and philosophical thoughts, especially regarding power and its dynamics. Using quantitative data from literature studies, we understand that cycle theory is a fundamental principle for Ibn Khaldun when looking at power dynamics and human civilization. Ibn Khaldun believes that human power and civilization have cycles like human life. Humans are born, grow, develop, mature and grow old and then die. According to Ibn Khaldun, power is also the same; nothing lasts forever, and everything has a final limit. Ibn Khaldun believes that the fundamental laws in social and political systems are not static but historical. The period for a civilization or power to survive depends on the strength of the Asabiyyah in society, state, culture, and the nation itself. Besides 'asabiyyah, moral strength is a pillar in maintaining civilization's progress and power. Morals are the soul of power and civilization. Their existence is like the soul for the body. Moral principles in exercising power also differentiate Ibn Khaldun from the pragmatic view of power and modern politics, which believes that politics does not have to be linked to moral values; it is the art of achieving power by any means. According to Ibn Khaldun, power is not merely the physical and worldly control authority over a country and region. Still, it functions as an instrument that guarantees the realization of God's vision for human civilization, namely the benefit of the people or the common good.